Impact of Autoimmune Demyelinating Brain Disease Sera on Pericyte Survival - Ulusoy, Canan (Noro Psikiyatr Ars, 2021)
INTRODUCTION: Multiple sclerosis (MS) is an autoimmune disease of the central nervous system (CNS) characterized by demyelination and brain pericyte dysfunction might be involved in MS pathogenesis Our aim was to evaluate whether the factors in serum affect pericyte survival. METHOD: C57BL/6 female mice were immunized with myelin oligodendrocyte glycoprotein (MOG) to induce experimental autoimmune encephalomyelitis (EAE). To confirm the animal model, the sera level of anti-MOG antibody in mice and platelet-derived growth factor-BB (PDGF-BB) in patients was measured by ELISA. Human brain vascular pericytes (HBVP) cell lines were incubated with sera of EAE mice and primer progressive MS (PPMS), seconder progressive MS (SPMS) and relapsing-remitting MS (RRMS) patients. The viability of HBVP is measured with Annexin V-FITC/propidium iodide staining with flow cytometry. RESULTS: Annexin V-FITC/propidium iodide staining with flow cytometry showed increased ratios of early apoptosis and decreased survival following incubation with sera of EAE and progressive MS. Levels of platelet-derived growth factor-BB were identical in serum and cerebrospinal fluids of patients with different forms of MS. CONCLUSION: Our results suggest that serum factors might contribute to progressive MS pathogenesis via pericyte dysfunction.